A New Gamma Odd Lindley Generalized-G Family of Distributions with Applications - Oluyede, Broderick; Warahena-Liyanage, Gayan (Thailand Statistician, 2026)
In this study, we present a new and generalized family of distributions referred to as the Gamma Odd Lindley Generalized-G (GOLG-G) distribution. Some structural properties of the new family of distributions including hazard rate function, quantile function, moments, incomplete moments, distribution of the order statistics and Renyi entropy are derived. The parameters of the new family of distributions are estimated via the method of maximum likelihood. A simulation study to examine the bias and mean square error of the maximum likelihood estimates and applications to real data sets to illustrate the usefulness and applicability of the generalized family of distributions are given.